Penerapan Regresi Logistik Biner pada Status Kesejahteraan Rumah Tangga di Provinsi Bali Tahun 2020 - Vinanda Sonya Permatasari; Lia Yuliana (Politeknik Statistika STIS, 2021)
Welfare is a target of all countries including Indonesia. Actions to achieve prosperity can be started by evaluating the region and following in the footsteps of other prosperous regions. Researchers chose Bali as a region that can be used as a role model in the field of welfare because of its success in achieving prosperity and reducing poverty. This study aims to determine the general description of household welfare and the effect of household characteristics on household welfare in Bali in 2020. The research unit of analysis used was households with working and temporarily unemployed household heads. The analytical method used is descriptive and binary logistic regression analysis. The results are the number of household members, gender of head of household, age of head of household, last education of household head, household business field, and main occupation sector of the household head have a significant effect on welfare in Bali in 2020.